Moral decision-making in patients with neurodegenerative diseases: a systematic review - Capitani, Giorgia; Lozzi, Daniele; Curcio, Giuseppe; Migliore, Simone (Frontiers in Psychology, 2026)
IntroductionMoral decision-making, a core component of social cognition, relies on integrating affective and cognitive processes supported by distributed neural networks. Neurodegenerative diseases disrupt these systems to varying degrees, offering unique models to investigate the neural bases of moral cognition. This review aimed to systematically examine moral decision-making deficits across neurodegenerative diseases, delineate disease-specific patterns of moral cognition impairment, and highlight conceptual and methodological gaps to inform future research and clinical assessment.MethodsA systematic search of PubMed, Web of Science, and Scopus was conducted for studies published up to January 2025, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines.ResultsSeventeen studies met inclusion criteria. Convergent evidence indicates that behavioral variant frontotemporal dementia (bvFTD) produces a distinctive utilitarian bias characterized by diminished empathy, emotional blunting, and impaired integration of intention and outcome, reflecting degeneration of the ventromedial prefrontal cortex, anterior insula, and amygdala within the salience and default mode networks. In contrast, Alzheimer’s disease (AD) patients typically preserve affective aversion to harm, suggesting relative sparing of limbic–ventromedial circuits despite conceptual and executive decline. Moral reasoning in Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS) remains largely intact unless frontotemporal involvement occurs, while dementia with Lewy bodies (DLB) manifests intermediate profiles marked by reduced cognitive theory of mind and aberrant moral affect.DiscussionThese findings delineate disease-specific patterns of moral dysfunction linked to network-level degeneration rather than global cognitive decline. Understanding these mechanisms holds translational relevance for early diagnosis, ethical capacity assessment, and the development of ecologically valid tools to monitor socio-emotional deterioration in neurodegenerative disorders.